(untitled) (Journal of Comparative & International Higher Education, 2022)
The COVID-19 pandemic has had a significant impact worldwide. However, comparative studies by country on this topic are limited. This paper explores the question: how has the COVID-19 pandemic affected higher education students, and which ones have been most impacted? Indonesia and Vietnam are our focus. We leveraged a rich set of data collected online from university students from both countries (n = 2600). We used regression analyses to measure students’ wellbeing, financial hardships, access to technology, and educational satisfaction. As expected, we found statistically significant differences between both countries except for the wellbeing domain. For within-country comparison, consistent for both countries, low-income students were less likely to access technology than their counterparts, and low-income students were more likely to experience financial distress. Indonesian first-gen students also showed a similar trend. We did not find consistent statistically significant estimates for students’ burnout measures in these two countries. Lastly, we observed a lower likelihood of satisfaction from rural and low-income students in Indonesia for their education during the pandemic. We provide our policy recommendations for both countries. Keywords: COVID-19 pandemic, comparative study, disadvantaged students, first-generation, higher education, low-income, rural